Food safety aspects of post-harvest fungicides used on citrus fruits - Buzás, Anna; Lányi, Katalin (GEORGIKON FOR AGRICULTURE, 2020)
The storage of fruits can be made safer by using fungicides that inhibit the development of moulds during transportation. Nice-looking fruits with longer shelf-life are basic consumer expectations, however, it is even more important that moulds may produce mycotoxins posing serious risk to human health. The most commonly used fungicides for this purpose are imazalil, thiabendazole, and prochloraz. The consumer awareness of these fungicides was surveyed by means of an electronic questionnaire. An LC-MS / MS method was developed and validated for measuring imazalil, thiabendazole, and prochloraz in various fruits. Various commercially available fruits were examined for these three compounds, and the effectiveness of the most popular fruit cleaning methods for removing these three compounds from the surface of fruits was also tested based on the results of the questionnaire. Imazalil was found also in products labelled as organic: on banana in a higher content, while on lemon and orange in a lower one, however these values were far below the MRLs for adults. Our experiments investigating the effectiveness of peel cleaning procedures showed that neither the cleaning was complete, nor the chemical efficacy of a cleaning method was in proportional to its popularity.
Keywords: post-harvest fungicides; citrus fruits; surface treatment